triangle with area 893 square
inches and base 38 inches?
Answer:
47
Step-by-step explanation:
Start by drawing the figure and labeling it with the given information. We are looking for the height of a triangle. The formula for the area of a triangle is A=12bh, where b is the length of the base and h is the height of the triangle. Substituting in the given information and solving for h, we find
A8938931947=12bh=12(38)(h)=h=h
The height is 47 inches.
Answer:
(0, 1).
Method 1 (Substitution):
Substituting our two y's, we get the following:
Thus, the only set of solutions is (0, 1). A quick sketch (either by hand or on Desmos) can confirm this.
Method 2 (Elimination):
We have two equations. We'll let the top one be equation 1 and the bottom one be equation 2. Eliminating as many variables as we can, we subtract (2) from (1) to get:
0 = 3x => x = 0.
So the only set of solutions is (0, 1).
Method 3 (Gaussian elimination):
We can place this in an augmented matrix and row reduce.
Row reducing this gives us:
This tells us that the only solution for x is x = 0 (since we read this as "3x = 0") and thus, the only solution we get is (0, 1).
Answer:
10353
Step-by-step explanation:
The given series is in arithmetic progression since the common difference is same which is 8.
To find the sum of series we can simply apply the formula'
S= n/2( first term + last term)
S is the sum and n is the number of terms
we also need to find the number of terms n
n = (last term- first term)/2 + 1
n= 51
s= 10353
Answer:
The domain is all real numbers and the range is all real numbers
Step-by-step explanation:
The distance travel on the x-axis, you will travel on the complete axis so the answer to the domain is all real numbers. For the range, the distance travel on the y-axis, you travel on the complete axis so the answer is all real numbers.
А. 900
ОО
B. 899
Explanation:
Replace n with 100 and simplify
f(n) = 9n-1
f(100) = 9(100)-1
f(100) = 900-1
f(100) = 899
The 100th term is 899
x/3-x-1/2≥1 a. x≤-3 b. x≥-3 c. x≤3 d. x≥3
Answer:
x ≤-9/4
Step-by-step explanation:
x/3-x-1/2≥1
Multiply each side by 6 to get rid of the fractions
6(x/3-x-1/2)≥1*6
2x -6x -3≥6
Combine like terms
-4x-3≥6
Add 3 to each side
-4x-3+3≥6+3
-4x ≥9
Divide each side by -4, remembering to flip the inequality
-4x/-4 ≤9/-4
x ≤-9/4